The Aquanaut: A Graphic Novel - Santat, Dan (New York, NY : Graphix, an imprint of Scholastic, 2022)
"Ever since her father was lost at sea, Sophia has been moping around Aqualand, a marine theme park. But Sophia's world is turned upside-down when an aquanaut breaks into the park's research lab.To her amazement, Sophia discovers that the aquanaut is not what it seems: inside lives a band of goofy sea creatures! And when they all realize that Aqualand is more sinister than advertised, Sophia is determined to help the aquanaut crew free the park's captive marine life before it's too late."--Provided by publisher.
Keywords: Orphans -- Comic books, strips, etc; Marine animals -- Comic books, strips, etc; Marine animals -- Comic books, strips, etc. -- Conservation; Endangered species -- Comic books, strips, etc. -- Conservation; Amusement parks -- Comic books, strips, etc; Girls -- Comic books, strips, etc; Orphans -- Fiction; Marine animals -- Fiction; Marine animals -- Fiction. -- Conservation; Endangered species -- Fiction. -- Conservation; Amusement parks -- Fiction; Girls -- Fiction; Cartoons and comics; Graphic Novel; Fantasy comics; Graphic novels; Comics (Graphic works)